(untitled) (Journal of Paediatric Surgeons of Bangladesh, 2015)
Spina bifida and Hydrocephalus is one of the most common malformations in Paediatric Surgery. Though the two diseases has their own way of presentation but Spina bifida is accompanied by hydrocephalus in 80 to 90% of cases and treatment protocol is interrelated. As a general paediatric surgeon of the third world country we are facing the challenging job in our day to day practice. The etiology, pathophysiology, diagnosis, treatment and prognosis is not well understood and gratifying. We dont have so much interest on the most vital but neglected birth defect. My aim of discussing this two entity at a time to show light on this malformation and make all paediatric surgeon a bit conscious about the disease process and treatment modalities. So that only referring the patient to a tertiary hospital is not the job of a paediatric surgeon rather we must come forward to prevent and treat this major morbid diseases with ourselves. As a paediatric surgeon our role is not to become a good general paediatric surgeon, also acquire proficiency on other speciality like urology, neurosurgery, orthopaedics, reconstructive & oncology. J. Paediatr. Surg. Bangladesh 3(1): 37-46, 2012 (January)